Association between depression and nonadherence to antiretroviral therapy in pregnant women with perinatally acquired HIV. - Sheth, Sangini S; Coleman, Jenell; Cannon, Tirza; Milio, Lorraine; Keller, Jean; Anderson, Jean; Argani, Cynthia (AIDS care, 2015)
Women with perinatally acquired HIV (PAH) face unique psychosocial challenges due to the presence of a lifelong chronic illness and often unstable living situations. With advances in HIV treatment, an increasing number of those with PAH are reaching childbearing age and becoming pregnant. Depression may be an important and common factor that complicates both treatment and pregnancy outcomes in this group. We conducted a retrospective cohort study in pregnant patients with PAH to determine if history of depression is associated with nonadherence to antiretroviral therapy (ART). We reviewed charts of women with PAH receiving prenatal care at a single institution from March 1995 to December 2012. ART nonadherence was measured by patient self-report of any missed doses in the third trimester. Demographic, obstetric, and HIV infection characteristics of patients with a history of depression (dPAH) were compared to patients without a history of depression. Nine pregnancies among 6 dPAH women and 14 pregnancies among 12 PAH women without a history of depression were identified. None of the dPAH women reported 100% adherence to ART in the third trimester while 57% of women without a history of depression reported strict adherence (p = 0.04). The mean HIV RNA level at delivery was higher among dPAH women (17,399 vs. 2966 copies/Ml; p = 0.03) and fewer reached an undetectable HIV RNA level (<400 copies/mL) at delivery (p = 0.03). We concluded that a history of depression may contribute to poor medication adherence and treatment outcomes among pregnant women with PAH. Focused attention on diagnosis and treatment of depression in the preconception period may lead to more optimal medication adherence.
Keywords: Adolescent; Adult; Anti-HIV Agents; Depression; Female; HIV Infections; Hospitals, University; Humans; Medication Adherence; Perinatal Care; Pregnancy; Pregnancy Complications, Infectious; Retrospective Studies; United States